Autonomous Vehicles: From Technology to Law and Regulation - Suhariyanto, Didik; Usman, Ridwan; Marlin, Syamsu; Kurnia, Mega Tri; Firman, La Ode Mohammad; Balogun, Shuaibu Alani; Ghazali, Ihwan (Engineering Science Letter, 2024)
The advent of autonomous vehicles marks a convergence of technological advancement, societal change, and regulatory evolution with profound implications. This transformative technology has shifted from science fiction to reality, sparking extensive discourse encompassing technological progress, legal intricacies, and ethical considerations. This scholarly exploration navigates the intricate terrain of autonomous vehicles, tracing their evolution from a technological marvel to a catalyst for profound changes in legal frameworks, regulations, and societal dynamics. Our journey begins by delving into the technological foundations and significant achievements that underpin autonomous vehicle development. This illuminates the complex algorithms, sensor arrays, and machine-learning capabilities driving these self-driving vehicles. Transitioning from technology, we delve into the intricate realm of law and regulation, where established norms of road safety, liability, and privacy intersect with autonomy's transformative potential. This paper scrutinizes the intricate network of legal frameworks and ethical considerations governing the testing, deployment, and daily operation of autonomous cars. With their integration into transportation systems gaining prominence, balancing innovation with regulation assumes critical importance. This study embraces technology, law, and regulation, aiming to understand the multifaceted dimensions arising when autonomous cars intersect with legal and ethical frameworks. We explore the dynamic nature of global regulatory paradigms, analyzing obstacles, achievements, and ethical dilemmas shaping progress. As we embark on this endeavor, our goal is to offer a valuable resource elucidating the intricate process of transitioning from technology to legal frameworks and regulations within the era of autonomous vehicles.